Feed Intake, Body Weight, Average Daily Gain, Feed Conversion Ratio and Carcass Characteristics of Helmeted Guinea Fowl Fed Varying Levels of Phane Meal (Imbrasia belina) as Replacement of Fishmeal under Intensive System - Nobo , G.; Moreki, J.C.; Nsoso, S.J. (International Journal of Poultry Science, 2012)
The objective of this study was to investigate the effect of feeding varying levels of Phane meal (Imbrasia belina) as a protein source on feed intake, body weight, average daily gain, feed conversion ratio and carcass characteristics of guinea fowl under intensive system up to 13 weeks of age. A total of 96 day old keets were randomly allocated to 4 treatment diets, which were replicated 4 times (n = 6/replicate). Dietary inclusion levels of Phane meal were 4.5%, 9% and 13.5% while control diet contained 3% fishmeal. Parameters measured were Feed Intake (FI), Body Weight (BW) and carcass dressed weight, Average Daily Gain (ADG), dressing percentage, Feed Conversion Ratio (FCR), carcass dressed weight and dressing percentage. The present results showed that FI increased significantly (p